2009
DOI: 10.1055/s-0028-1087355
|View full text |Cite
|
Sign up to set email alerts
|

Hypervalent Aryl-, Alkynyl-, and Alkenyl-λ³-bromanes

Abstract: The chemistry of hypervalent organo-l 3 -bromanes with two carbon atom ligands is summarized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 19 publications
0
23
0
1
Order By: Relevance
“…Ochiai has recently included treatment of hypervalent bromine chemistry within a broader treatise 63 and a specific review of hypervalent organo-l 3 -bromanes. 64 Wirth and coworkers have published an account focusing on the unique applications of (diaryl)-l 3 -bromanes, aryl(alkynyl)-l 3 -bromanes and aryl(alkenyl)-l 3 -bromanes. 65 Cyclopent-1-enyl-(aryl)-l 3 -bromanes were prepared by low temperature ligand exchange of p-CF 3 C 6 H 4 BrF 2 with potassium cyclopentenyltrifluoroborate in MeCN.…”
Section: Hypervalent Halogen Compoundsmentioning
confidence: 99%
“…Ochiai has recently included treatment of hypervalent bromine chemistry within a broader treatise 63 and a specific review of hypervalent organo-l 3 -bromanes. 64 Wirth and coworkers have published an account focusing on the unique applications of (diaryl)-l 3 -bromanes, aryl(alkynyl)-l 3 -bromanes and aryl(alkenyl)-l 3 -bromanes. 65 Cyclopent-1-enyl-(aryl)-l 3 -bromanes were prepared by low temperature ligand exchange of p-CF 3 C 6 H 4 BrF 2 with potassium cyclopentenyltrifluoroborate in MeCN.…”
Section: Hypervalent Halogen Compoundsmentioning
confidence: 99%
“…8,9 On the other hand, chemistry of the related group 17 N-sulfonylimino-l 3 -bromanes has not been developed until recently, because a method for their syntheses was not available. In the past four years, our research projects directed toward the developing of hypervalent organo-l 3 -bromane chemistry 10 have been focused on that of N-sulfonyliminol 3 -bromane. In this feature article, we summarize the recent advances in N-sulfonylimino-l 3 -bromane chemistry, including preparation, molecular structure and reactions developed recently in Tokushima and Wakayama.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Hypervalent bromine derivatives with the general structures 4-6 (Scheme 2) have been reported. [5] The ligand exchange proceeds, as in l 3 -iodanes, [6] by a lowenergy and hence rapid addition-elimination process. Reaction of bromine trifluoride (3), a highly toxic and extremely reactive liquid, with arylstannanes, arylmercury, or arylboron compounds leads readily to (diaryl)-l 3 -bromanes of type 4 at low reaction temperatures (Scheme 3).…”
mentioning
confidence: 99%
“…Even triflates can be used to access previously unknown alkynyltriflates 10. [5] Ochiai, Frohn, and co-workers found that also alkynylstannanes can react in uncatalyzed reactions with 5 to produce diynes 13-a reaction exclusive to l 3 -bromanes. This reaction proceeds by an initial Michael addition of the alkynylstannane to give 11 and a subsequent reductive elimination of the bromine moiety to yield an alkylidene carbene intermediate 12.…”
mentioning
confidence: 99%